2014
DOI: 10.1002/2014ja019806
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fluctuations embedded in dipolarization inside geosynchronous orbit and their associated selective acceleration of O+ ions

Abstract: We study magnetic fluctuations embedded in dipolarizations in the inner magnetosphere (a geocentric distance of ≤6.6 R E ) and their associated ion flux changes, using the Engineering Test Satellite VIII and Active Magnetospheric Particle Tracer Explorers/CCE satellites. We select seven events of dipolarization that occur during the main phase of magnetic storms having a minimum value of the Dst index less than −40 nT. It is found that (1) all of the dipolarization events are accompanied by strong magnetic flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 56 publications
3
48
1
Order By: Relevance
“…Mass-dependent acceleration may be possible in the plasma sheet with magnetic and electric field perturbations (e.g., Catapano et al, 2016), in the reconnection region and around the separatrix between closed and open magnetic fields (where the Hall electric field exists; Liang et al, 2017), around a dipolarization front (i.e., a reconnection jet front) where the magnetic field increases in less than seconds and a strong electric field is thus induced (Runov et al, 2015), near the transition region from the stretched magnetic field to the dipole-like field where a fast flow associated with reconnection slows down and the electric field is induced by the magnetic field pileup (Nakayama et al, 2016). Possible waves are dispersive Alfvén waves (e.g., Chaston et al, 2016), which can accelerate O+ that are simultaneously extracted from the topside ionosphere and/or preexist on the same field lines; waves/fluctuations with a frequency range of electron-ion cyclotron waves (e.g., Nosé et al, 2014); and ULF waves (e.g., Mitani et al, 2018;Oimatsu et al, 2018), which can resonate with drifting and bouncing ring current ions. However, as higher-energy O+ are more difficult to transport to the inner magnetosphere, it is still a controversial issue whether a large number of those accelerated O+ can penetrate to around/inside geosynchronous orbit.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Mass-dependent acceleration may be possible in the plasma sheet with magnetic and electric field perturbations (e.g., Catapano et al, 2016), in the reconnection region and around the separatrix between closed and open magnetic fields (where the Hall electric field exists; Liang et al, 2017), around a dipolarization front (i.e., a reconnection jet front) where the magnetic field increases in less than seconds and a strong electric field is thus induced (Runov et al, 2015), near the transition region from the stretched magnetic field to the dipole-like field where a fast flow associated with reconnection slows down and the electric field is induced by the magnetic field pileup (Nakayama et al, 2016). Possible waves are dispersive Alfvén waves (e.g., Chaston et al, 2016), which can accelerate O+ that are simultaneously extracted from the topside ionosphere and/or preexist on the same field lines; waves/fluctuations with a frequency range of electron-ion cyclotron waves (e.g., Nosé et al, 2014); and ULF waves (e.g., Mitani et al, 2018;Oimatsu et al, 2018), which can resonate with drifting and bouncing ring current ions. However, as higher-energy O+ are more difficult to transport to the inner magnetosphere, it is still a controversial issue whether a large number of those accelerated O+ can penetrate to around/inside geosynchronous orbit.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…There has been a recent suggestion that the thermal O + torus can be accelerated by nonadiabatic mechanisms to ring current energies . Nosé et al (2014), showed that the magnetic fluctuations associated with dipolarizations inside 6.6 R E have a frequency close to the O + gyrofrequency, and can preferentially accelerate the O + to 5-10 keV. The population from 1-10 keV can also drift in from the nightside plasma sheet, so the importance of the energization is not clear.…”
Section: Ring Currentmentioning
confidence: 99%
“…Even around the time of the proton injection event at ~20:00 UT, no sharp increase in the z component was seen. The B z profile is different from typical dipolarization events observed in the inner magnetosphere [ Nosé et al ., , ]. The proton injection was slightly energy‐dispersed as shown in Figure .…”
Section: Impulsive Injections During Storm Main Phasementioning
confidence: 99%